Evaluation of Interleukin-6 (IL-6) Level in Serum of Type 2 Diabetes Patients and Correlation with Neuropathy (Iraqi Journal of Medical Sciences, 2024)
Background: Diabetic polyneuropathy (DPN) is a prevalent long-term consequence of type 2 diabetes mellitus (T2DM). The cause of DPN is still a subject of controversy, but it is possible that proinflammatory cytokine mediators such as interleukin-6 (IL-6) play a role.Objective: To assess the correlation between pro-inflammatory marker (Il-6) and the development of DPN in T2DM patients. Methods: A case-control study, involved randomly selected 140 T2DM patients attended to Al-Numan Teaching Hospital at Baghdad during the period from October 2023 to January 2024. Their age ranged from 25 to 80 years, 57 males and 83 females. The patients have been divided into two groups; those with DPN and diabetic patients without neuropathy. For both groups' patients, whole blood sample was centrifuged and serum was prepared and used as biological material for IL-6 levels determination by enzyme-linked immunosorbent assay (ELISA) technique. This study compared IL-6 levels between the two groups.Results: The mean age of study samples was 58.69±10.51 years. The female to male ratio 1.45:1, as well as females were dominant among cases and that of controls group, but such differences were not statistically significant. The mean value of IL-6 was found to be significantly higher among cases group than that of controls group (117.68±27.38 vs. 57.3±13.24 pg/ml) respectively. The optimal cutoff value of IL-6 for detection of diabetic patients with high risk of neuropathy development was 72.46 pg/ml with sensitivity of 97.1%, and specificity of 87.1% with good area under the ROC curve (AUC) (P
Keywords: Diabetic neuropathy; IL6; type 2 diabetes mellitus